A Microwave Step for the Synthesis of 4,5-Dicyanopyridazine: A Great Forerunner to Phthalocyanines - Silva, Charles Biral; de Oliveira, Hueder Paulo Moisés; Ribeiro, Anderson Orzari (Orbital: The Electronic Journal of Chemistry, 2018)
4,5-Dicyanopyridazine (DCP) shows unexpected reactivity with dienophiles via Hetero Diels-Alder. Reactions involving this compound and alkynes or enamines was already described, open possibilities to synthesize precursors for important macromolecules, like phthalonitriles used in phthalocyanines synthesis. Herein, we present a microwave synthetic step in the DCP synthetic route in order to minimize the time to synthesize this compound.DOI: http://dx.doi.org/10.17807/orbital.v10i2.1133